Social media’s impact on Generation Z’s purchasing behavior of sustainable products - Tan, Trinh Le; Trang, Dao Thi Dai (International Journal of Emerging Trends in Social Sciences, 2023)
The aim of this study is to evaluate the effects of social networks on the consumption behavior of sustainable products among Generation Z. Social networks have evolved into important technologies, making them an unavoidable option for Generation Z and the human race in general. Therefore, it is necessary to comprehensively assess how social networks have influenced the consumption behavior of Gen Z toward sustainable products in order to improve the process of community implementation while improving the quality of social networks and the durability of products. A literature review was conducted of studies linked to the suggested study model, which includes a mix of social network models and external variables influencing Gen Z's purchase of sustainable products via social networks. The suggested model was then tested on a sample of 100 Vietnamese students. Social networking techniques were used to study and evaluate the dataset. The report advises that managers and marketers should employ social media marketing tactics to communicate with Gen Z customers and promote the value of sustainability. Management and marketers should also provide sustainability information and promote sustainable goods on popular social media platforms, such as Instagram, Facebook, Twitter, and TikTok.